Yeasts from the oral cavity of children with AIDS: exoenzyme production and antifungal resistance (Pesquisa Odontológica Brasileira, 2003)
The oral fungal microbiota of 30 children with AIDS, of both genders, aged from two to six years, receiving outpatient treatment, was evaluated and compared with that of a control group composed of 30 healthy subjects with matching ages and genders. Virulence factors, such as exoenzyme production, and susceptibility to five antifungal agents using an E-Test kit were evaluated. C. albicans predominated over other species in the AIDS group, showing a higher production of proteinase and phospholipase when compared with that observed in the control group. In this study few clinical manifestations of and low selectivity for C. albicans (23.3%) were observed in the AIDS group. The enzymatic studies showed that 53.8% of the AIDS strains were strongly positive whereas only 33.3% of the non-AIDS strains were positive. Amphotericin B was the most effective drug among the antifungal agents tested against C. albicans. The frequency, selectivity and level of exoenzyme production by C. albicans suggest a higher pathogenicity in the AIDS children than in the control children.